Last updated at Sept. 14, 2018 by Teachoo
Transcript
Ex9.2 , 10 If the sum of first p terms of an A.P. is equal to the sum of the first q terms, then find the sum of the first (p + q) terms. We know that Sn = n/2 ( 2a + (n 1)d ) Where, Sn = sum of n terms of A.P. n = number of terms a = first term and d = common difference Now, Sum of first p terms = Sp = p/2 [2a + (p 1)d] Sum of first q terms = Sq = q/2 [2a + (q 1)d] It is given that Sum of first p terms = Sum of first q terms p/2 [2a + (p 1)d] = q/2 [2a + (q 1)d] p[2a + (p 1)d] = (2 )/2[2a + (q 1)d] p[2a + (p 1)d] = q[2a + (q 1)d] 2ap + pd(p 1) = 2aq + qd (q 1) 2ap 2aq = qd (q 1) pd(p 1) 2a(p q) = d[(q 1)q (p 1)p] 2a(p q) = d[q2 q (p2 p)] 2a(p q) = d[q2 q p2 + p] 2a(p q) = d[q2 p2 + p q] 2a(p q) = d [ q2 + p2 p + q] 2a(p q) = d [p2 q2 (p q)] 2a(p q) = d [(p q) (p + q) (p q)] 2a(p q) = d(p q) [p + q 1] 2a(p q) + d(p q) [p + q 1] = 0 (p q) [2a + d(p + q 1)] = 0 2a + d(p + q 1) = 0 Now, finding sum of first (p + q) terms We know that, Sum of n terms = n/2 [2a + (n 1)d] For sum of (p + q) terms, we put n = (p + q) Sum of (p + q) term is = (p + q)/2 [2a + (p + q 1)d] = (p + q)/2 0 = 0 Hence, sum of (p + q) term is 0
Ex 9.2
Ex 9.2, 2
Ex 9.2, 3 Important
Ex 9.2, 4
Ex 9.2, 5 Important
Ex 9.2, 6
Ex 9.2, 7 Important
Ex 9.2, 8
Ex 9.2, 9 Important
Ex 9.2, 10 You are here
Ex 9.2, 11 Important
Ex 9.2, 12
Ex 9.2, 13
Ex 9.2, 14 Important
Ex 9.2, 15 Important
Ex 9.2, 16 Important
Ex 9.2, 17
Ex 9.2, 18 Important
Ex 9.2
About the Author